Melatonin: Manager of psychosomatic and metabolic disorders in polymorbid cardiovascular pathology - Partsernyak, Alexander S.; Polyakova, Victoria O.; Trufanov, Artem G.; Medvedev, Dmitriy S.; Trotsyuk, Dina V.; Markin, Kirill; Kurasov, Evgeniy S.; Kuznetsova, Evgeniya V.; Krasichkov, Alexander S. (Frontiers in Neuroscience, 2022)
Objectives. To investigate the relationship between changes in circadian patterns of melatonin and clinical manifestations of polymorbid cardiovascular pathology in young men and to analyze the effectiveness of their complex treatment. Materials and methods. We made the immunohistochemical analysis of epiphysis tissues from autopsies of 25 men aged 32-44 with polymorbid cardiovascular pathology and metabolic syndrome who had died as a result of ischemic cardiomyopathy and 25 persons after the car accident as a control group. Then, 93 young men aged 35-44 with polymorbid cardiovascular pathology, metabolic syndrome, and depressive spectrum disorders were divided into three groups: 1) standard therapy; 2) standard therapy and psychotherapy sessions; 3) standard therapy in combination with psychotherapeutic and psychophysiological visual and auditory correction sessions. The control group included 24 conditionally healthy male volunteers. Before and after the treatment, we studied the anthropometric status, lipid and carbohydrate metabolism indicators, the level of melatonin, the degree of nocturnal decrease in blood pressure, and the relationship of these indicators with circadian variations of melatonin. Results. Young polymorbid patients who died from ischemic cardiomyopathy have a lower expression of melatonin type 1 and 2 receptors. All patients with polymorbid cardiovascular pathology showed a decrease in the nocturnal melatonin fraction and a correlation with higher severity of depressive (r = - 0,72) and anxiety (r = - 0,66) symptoms. Reduced values of the 6-hydroxymelatonin sulfate (6-SM) in the 1st (r = 0,45), 2nd (r = 0,39) and 3rd (r = 0,51) groups before treatment was associated with periods of increased blood pressure. The achievement of melatonin reference values and normalization of biochemical parameters of carbohydrate and lipid metabolism, daily blood pressure profile, and psychophysiological state were noted in all three patients' groups, with a more pronounced effect in group 3. Conclusion. Low nocturnal melatonin levels are associated with greater severity of clinical symptoms and a higher risk of death in patients with polymorbid cardiovascular pathology. Therefore, comprehensive therapy may be more effective for correcting this disease.